PENGARUH DANA ALOKASI UMUM DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROVINSI DAERAH ISTEMEWA YOGYAKARTA TAHUN 2011-2016 - Argo A. P Fahma A. P; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2017)
The debate on the need for capial in emplementing equitable distribution of inter-reginonal financial capacitu for the implaementation of decenralizion is an explanation of General Alloction fund. While District Own Source Revenue is revenue derived from thr levy or the result of the existing power sumbet in each region.the purpose of this study to find out how ig General Alloction fund and District Own Source Revenue affect the economic growt of each distrik/city of DIY Province. The analytical tools used in this study testing the suitability of the model, and hypothesis teasting with the F test, T test, and te determinant coficien test (R2) at the error rate α = 5%.. Result of regression analysis of panel data with selected model is gixed effect. While the value of coefficient of determination(R2) is 0,89 or 89% it shows that the variable capabilities of General Alloction fund and District Own Source Revenue explain affect ecnmic growth.Keywords: General Alloction fund, District Own Source Revenue, Economic Growth